Arthroscopic Bankart versus open Latarjet as a primary operative treatment for traumatic anteroinferior instability in young males: a randomised controlled trial with 2-year follow-up - Kukkonen Juha; Elamo Sami; Flinkkilä Tapio; Paloneva Juha; Mäntysaari Miia; Joukainen Antti; Lehtinen Janne; Lepola Vesa; Holstila Milja; Kauko Tommi; Äärimaa Ville; FINNISH (Finnish Instability Shoulder Study) Investigators (United Kingdom, 2022)
Objectives: To compare the success rates of arthroscopic Bankart and open Latarjet procedure in the treatment of traumatic shoulder instability in young males.
Design: Multicentre randomised controlled trial.
Setting: Orthopaedic departments in eight public hospitals in Finland.
Participants: 122 young males, mean age 21 years (range 16-25 years) with traumatic shoulder anteroinferior instability were randomised.
Interventions: Arthroscopic Bankart (group B) or open Latarjet (group L) procedure.
Main outcome measures: The primary outcome measure was the reported recurrence of instability, that is, dislocation at 2-year follow-up. The secondary outcome measures included clinical apprehension, sports activity level, the Western Ontario Shoulder Instability Index, the pain Visual Analogue Scale, the Oxford Shoulder Instability Score, the Constant Score and the Subjective Shoulder Value scores and the progression of osteoarthritic changes in plain films and MRI.
Results: 91 patients were available for analyses at 2-year follow-up (drop-out rate 25%). There were 10 (21%) patients with redislocations in group B and 1 (2%) in group L, p=0.006. One (9%) patient in group B and five (56%) patients in group L returned to their previous top level of competitive sports (p=0.004) at follow-up. There was no statistically significant between group differences in any of the other secondary outcome measures.
Conclusions: Arthroscopic Bankart operation carries a significant risk for short-term postoperative redislocations compared with open Latarjet operation, in the treatment of traumatic anteroinferior instability in young males. Patients should be counselled accordingly before deciding the surgical treatment.
e counselled accordingly before deciding the surgical treatment.\nNCT01998048.